KONSERVATISME AKUNTANSI, CORPORATE GOVERNANCE, DAN KUALITAS LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BEI) - FEBIANI, SISKA (Universitas Katolik Widya Mandala Surabaya, 2012)
Financial statements describes the performance of corporate management in managing the resources entrusted. In an effort to refine those statements was born the concept of conservatism. The concept of conservatism that will affect the quality of the resulting company's earnings, which can increase or decrease the quality of earnings. Besides that the influence of corporate governance (independent commissioners, institutional ownership, managerial ownership, quality audit) may also affect the quality of a company's earnings. This research aims to examine and analyze the differences in the quality of corporate earnings in the conservative and less conservative, and the influence of corporate governance on the quality of corporate earnings. The data used in the form of annual financial statement data of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period 2008-2010. Sources of data in this research is secondary data from the manufacturing company's financial statements published by the BEI in http://www.idx.co.id/ site and also share data on the Indonesian Capital Market Directory (ICMD). The results showed that there is a difference between the quality of earnings (which diproksikan coefficient ERC) and non-corporate conservatism conservatism. Independent Commissioner (KI), Institutional Ownership (Kinst), Managerial Ownership (KM), and Quality Audit (KA) significantly influence the coefficient of ERC.